Direct diode-pumped Kerr-lens mode-locked Ti:sapphire laser - Durfee, Charles G. (Optical Society of America, 2012)
We describe a Ti:sapphire laser pumped directly with a pair of 1.2W 445nm laser diodes. With over 30mW average power at 800 nm and a measured pulsewidth of 15fs, Kerr-lens-modelocked pulses are available with dramatically decreased pump cost. We propose a simple model to explain the observed highly stable Kerr-lens modelocking in spite of the fact that both the mode-locked and continuous-wave modes are smaller than the pump mode in the crystal.